2006
DOI: 10.1063/1.2357701
|View full text |Cite
|
Sign up to set email alerts
|

Single phase nanocrystalline GaMnN thin films with high Mn content

Abstract: Ga 1 − x Mn x N thin films with a Mn content as high as x=0.18 have been grown using ion-assisted deposition and a combination of Rutherford backscattering spectroscopy and nuclear reaction analysis was used to determine their composition. The structure of the films was determined from x-ray diffraction, transmission electron microscopy, and extended x-ray absorption fine structure (EXAFS). The films are comprised of nanocrystals of random stacked GaMnN and there is no evidence of Mn-rich secondary phases or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In previous work we reported that the Mn ions show an extended x-ray absorption fine structure pattern that establishes they have a coordination that is identical to that of the Ga in these and in Mn-free GaN. 30 They have four N nearest neighbors and 12 cation second-nearest neighbors. We see no evidence at all for secondary phases such as rocksalt-structure MnN, which is an antiferromagnetic metal with T N = 400°C.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…In previous work we reported that the Mn ions show an extended x-ray absorption fine structure pattern that establishes they have a coordination that is identical to that of the Ga in these and in Mn-free GaN. 30 They have four N nearest neighbors and 12 cation second-nearest neighbors. We see no evidence at all for secondary phases such as rocksalt-structure MnN, which is an antiferromagnetic metal with T N = 400°C.…”
Section: Methodsmentioning
confidence: 89%
“…29 Both the composition and structure of these films have been carefully examined. 30 The compositional details were determined by a combination of Rutherford backscattering spectroscopy, nuclear reaction analysis, and secondary-ion mass spectroscopy, with the results summarized in Table I. The surface of the films is partially oxidized, resulting in the few percent O content that is detected in some samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the preparation of ferromagnetic Ga 1−x Mn x N using the molecular beam epitaxy ͑MBE͒ technique is quite recent [3][4][5][6][7] and has attracted the attention of several groups concerning the mentioned as well as other techniques. [8][9][10][11][12][13][14] In a recent report we have described the preparation of Ga 1−x Mn x N nanocrystalline films using the sputtering technique. 15 The low substrate temperature, allowed by the plasma breaking of N 2 molecules and the use a metallic Ga target covered by small Mn pieces, makes the preparation and Mn incorporation simple and versatile.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for the excellent application prospect of Ga 1−x Mn x N, there has been a strong research effort on it. Different Mn ions existence forms in the host GaN lattice and the corresponding ferromagnetic induction mechanism [9][10][11][12][13][14] were reported with different growth methods [15][16][17][18][19][20]. Despite many investigations, the origin and control of ferromagnetism in Ga 1−x Mn x N are, arguably, the most controversial research topics in material science and condensed-matter physics today and there is still much work to do in fabrication and characterization of relevant materials.…”
Section: Introductionmentioning
confidence: 97%